Energy management software - Jie, Yongqiang (2009)
Due to the emergence of the current energy crisis, the need to reduce energy consumptions is critical. One of the ways of reducing energy is by having an efficient management program. Energy audits can help to identify the potential energy consumption of the building or facility that it is using currently. The program is able to come up with some suggestions and methods to reduce energy consumptions efficiently. In this project, software is being used to help energy auditors to carry out energy management saving objectives. The project is build upon foundations of database and software engineering. In the database engineering, the approach is based on the database management system, the relational database and the normal forms methods. The software engineering method includes process model, requirement engineering, entity relational modeling, data flow, state diagram design, sequence diagram design, activity diagram design and software testing process. With the use of the above methods, different scenarios and use cases are used. Use Cases are used to identify different user functionalities and Scenarios which predict the possible outcomes of each action being implemented. With the implementation of the software, the program would be able to simplify many different steps used in measuring the energy usage. In this particular program, there are six primary functions: The user templates, Self creation database, Graphing of data, Help file and External database link. The results from the software will be able to enhance their work performance as the steps are being simplified and less time consuming to generating huge volumes of unprocessed reports. This is generally useful as more time can be saved and improves productivity.